Table 1_In-silico pharmacological insights into the therapeutic potential of microRNAs for microplastic-associated cancers.docx - Akmaral Baspakova (17961710) (2025)
Microplastics (MPs) are increasingly implicated in cancer biology through effects on gene expression, stress responses, and treatment susceptibility; however, causal links remain provisional. We systematically screened PubMed and Google Scholar (through September 2025) to identify cancer-related genes reported to be altered by MP exposure and then evaluated microRNAs (miRNAs) with anticancer activity that may target those genes. Mature miRNA sequences were retrieved from RNAcentral and assessed against MP-altered genes using RNAhybrid for target-site prediction and minimum free-energy (mfe) hybridization. MPs were reported to modulate genes across multiple tumor types—including breast, gastric, liver, lung, colorectal, cervical, pancreatic, and skin. In silico analyses identified candidate miRNAs with favorable mfe values for these targets, including miR-483-3p, miR-365, miR-331-3p, miR-138-5p, miR-760, miR-1-3p, miR-665, miR-490-3p, miR-370-3p, miR-520a, miR-638, miR-559, miR-532-3p, miR-593-5p, and miR-29b. These interactions suggest putative avenues to counter MP-associated oncogenic programs and therapy resistance. Because mfe predictions do not establish functional regulation, all findings should be interpreted as hypothesis-generating. Priorities for validation include reporter assays, gene/protein modulation, phenotypic rescue, and in vivo testing in MP-exposed models. Collectively, our results nominate miRNAs as candidate tools to interrogate and potentially mitigate MP-associated carcinogenic mechanisms.